Vladimir F. Tsel - Svetlana V. Bragina (Travmatologiâ i Ortopediâ Rossii, 2023)
The article is dedicated to the 125th anniversary of the birth of Doctor of Medical Sciences, professor V.F. Tsel. He was the founder of the school of surgery, traumatology and orthopedics in Arkhangelsk, who made a huge contribution to the formation and development of the northernmost medical institute.